Effect of returns on microstructure and mechanical properties of Al-Cu based alloys - Li Min; Wang Hongwei; Wei Zunjie (China Foundry, 2010)
It is well known that maximal utilization of the returns can be beneficial for cost reduction, preservation of natural resources and protection of the environment, by making them into recycled Al-Cu alloys. In this study, the influences of returns on the microstructure and mechanical properties of Al-Cu alloys have been investigated by means of optical microscopy and scanning electron microscopy. The results showed that the returns could be used to produce recycled Al-Cu alloys with fine and uniform microstructure and excellent mechanical properties, including ultimate tensile strength, yield strength and ductility. It was found that the maximum performance of the recycled Al-Cu alloy in their properties could be achievable when the returns content was 20wt.%, which gave 219 MPa, 87.16 MPa and 12.15% at as-cast state, and 525 MPa, 445.3 MPa and 14.14% after heat treated, in their tensile strengths, yield strengths and elongations, respectively. These values were much higher than those of primary alloy.